Manajemen Tantrum Seumur Hidup : Integrasi Psikologi Modern Dan Pendidikan Islam Dalam Regulasi Emosi Anak Hingga Dewasa - Agustini, Dewi (Lisyabab : Jurnal Studi Islam dan Sosial, 2025)
Tantrum is commonly understood as an explosive emotional reaction often seen in early childhood, but this behavior can persist into adulthood if not addressed through early emotional regulation. This study explores tantrum as a lifelong psychological phenomenon influenced by parenting styles, emotional development, and spiritual imbalance. Using a qualitative literature review method, the study synthesizes theories from Western psychology (Gross, Erikson, Beck) and Islamic perspectives (Al-Ghazali) to explain the continuity and transformation of tantrum behavior from early childhood to adulthood. It identifies critical factors such as authoritarian or permissive parenting, poor coping mechanisms, and the lack of spiritual grounding as contributors to emotional dysregulation. The paper proposes integrative strategies including cognitive-behavioral therapy (CBT), mindfulness, and Islamic spiritual practices to prevent and manage tantrum behavior. The findings emphasize the need for early interventions, holistic education, and community-based support systems to develop emotional resilience and prevent maladaptive emotional outbursts in adulthood. This research contributes to the growing discourse on emotional regulation by offering a culturally and spiritually contextualized framework for tantrum management across the lifespan.